Apathy, anhedonia and cognitive dysfunction: common symptoms of depression and neurological disorders - D. S. Petelin; S. P. Bairamova; O. Yu. Sorokina; I. N. Niinoja; A. B. Lokshina; B. A. Volel (Неврология, нейропсихиатрия, психосоматика, 2022)
Depression is one of the most common mental disorders in neurological practice. Among other symptoms of depression, a symptom complex represented by apathy, anhedonia, and cognitive impairment plays an important role. This review presents the clinical characteristics of the symptoms described above and discusses modern neurochemical and neuroimaging concepts of their pathogenesis. The problem of pathogenetically substantiated therapy of depression with a predominance of apathy, anhedonia and cognitive impairment is discussed. Fundamental and clinical arguments are presented in favor of the high efficacy of vortioxetine in depression with a predominance of apathy, anhedonia, and cognitive impairment.